Developments in public transport governance in the Netherlands; the maturing of tendering. (September 2018) - Veeneman, Wijnand
Abstract: In 2001, competitive tendering was introduced for most concessions in the Netherlands, to be carried out by regional authorities. These authorities received a great deal of freedom to implement the tendering in the way they saw fit. Over the years, issues arose that challenged the effectiveness of the tendering approaches. For example, operators were overincentivised to low prices, the administrative burden of tendering proved high, service across concession boundaries was poor, cooperation between authorities and operators was poor. Even though the effect of these issues on patronage and efficiency were hard to distinguish from bigger trends, it is clear that tendering has matured. This article, as its precursors in earlier Thredbo conferences, captures these issues and the lessons drawn over the last 15 years and shows in what phases tendering has matured, based on the Dutch experience, that could help other authorities in the process of maturing their tendering of public transport. Key theme has been integration after the fragmentation that tendering brought through strict definition of roles, formal procedures, small and uni-modal concessions.